2021
DOI: 10.3390/cancers13143602
|View full text |Cite
|
Sign up to set email alerts
|

Lineage Plasticity in Cancer: The Tale of a Skin-Walker

Abstract: Lineage plasticity, the switching of cells from one lineage to another, has been recognized as a cardinal property essential for embryonic development, tissue repair and homeostasis. However, such a highly regulated process goes awry when cancer cells exploit this inherent ability to their advantage, resulting in tumorigenesis, relapse, metastasis and therapy resistance. In this review, we summarize our current understanding on the role of lineage plasticity in tumor progression and therapeutic resistance in m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 223 publications
(292 reference statements)
0
14
0
Order By: Relevance
“…Among 14 patients who underwent therapy, only three of them evolved to an SCNC phenotype from an adenocarcinoma phenotype, with varied levels of loss of AR signaling. Further, analysis of 176 primary and metastatic prostate tumors revealed that both phenotypes (adenocarcinoma, SCNC) could coexist for a patient in distinct metastatic lesions, thereby indicating lineage plasticity . In another prostate cancer study, tissue samples from the patients who underwent radical prostatectomy were analyzed using an artificial intelligence (AI) based method .…”
Section: Spatial Transcriptomics In Cancermentioning
confidence: 99%
“…Among 14 patients who underwent therapy, only three of them evolved to an SCNC phenotype from an adenocarcinoma phenotype, with varied levels of loss of AR signaling. Further, analysis of 176 primary and metastatic prostate tumors revealed that both phenotypes (adenocarcinoma, SCNC) could coexist for a patient in distinct metastatic lesions, thereby indicating lineage plasticity . In another prostate cancer study, tissue samples from the patients who underwent radical prostatectomy were analyzed using an artificial intelligence (AI) based method .…”
Section: Spatial Transcriptomics In Cancermentioning
confidence: 99%
“…Distinct CNV trends in the same chromosomal region were observed in different patients, whereas they were approximately consistent in the same patient, demonstrating both intertumoral heterogeneity and inter-lesional consistency. Lineage plasticity, enabling the switch of cells from one phenotypic state to another, has been proposed as a source of ITH in cancer [ 48 ]. In primary NSCLC, both CNV and mitochondrial mutation-based lineage tracking analyses based on scRNA-seq data clearly showed that mixed-lineage and single-lineage tumor cells in the same patient originated from common tumor ancestors rather than from different origins [ 49 ].…”
Section: New Insights Into Cancer Immunotherapy Based On Ai-assisted ...mentioning
confidence: 99%
“…Under intrinsic factors and extrinsic signals, the lineage of cells is gradually restricted by a subsequent step of highly regulated differentiation, which is normally irreversible. However, leukemia cells can hijack this regulatory system and take advantage of lineage plasticity to avoid lineage-specific antigen targeting by CAR-T cells, resulting in resistance and relapse (Thankamony et al, 2021). Lineage switch is defined as a process by which leukemia cells convert into different lineages at relapse compared to the initial diagnosis, with a transformation of cell morphology and immune types.…”
Section: Lineage Switchmentioning
confidence: 99%